REGULATION OF THE MANAGEMENT OF PRODUCTION AND CONSUMPTION WASTE: ECONOMIC AND LEGAL INSTRUMENTS - Kaymakova,; Igorevna Stepanova, Diana; Azitov, Rustam; Ivanovna Nosenko, Lidia; Dmitriyevich Sekerin, Vladimir; Evgenevna Gorokhova, Anna (Revista Inclusiones, 2020)
In the presented article, legal and economic mechanisms of the waste management regulation in the Russian Federation are examined. The relevance of this topic is conditioned by the significant damage to the environment due to the accumulation of waste and insufficient regulation of this problem by the state. In Russia, problems of environmental pollution by household and industrial waste from year to year become more and more urgent and demand the fastest way to solve, however, the situation changes only for the worse. At the same time, this problem has long been successfully resolved in several countries. The purpose of this article is to analyze the problematic aspects of waste disposal in the Russian Federation and find ways to solve them. The results of the activities carried out in the field of environmental protection are analyzed. The current legislation of the Russian Federation regulating the waste management and opinions of researchers on the existing problems of regulation are investigated.